2010
DOI: 10.1111/j.1600-0897.2010.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral ssRNA Induces First Trimester Trophoblast Apoptosis through an Inflammatory Mechanism

Abstract: Problem-Infection during pregnancy represents a significant cause of mobility and mortality. While viruses pose a major threat, little is known about their effect on early pregnancy, or the mechanisms involved. The objective of this study was to characterize the trophoblast response following exposure to viral ssRNA.Method of study-First trimester trophoblast cells were treated with or without viral ssRNA. Cytokine production was measured by multiplex analysis and ELISA. Apoptosis was determined using Hoescht … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
(114 reference statements)
2
48
0
1
Order By: Relevance
“…Data from trophoblast cell lines, including BeWo cells, dominate previous reports on TLR function in early gestational trophoblasts (Komine-Aizawa et al, 2008, Klaffenbach et al, 2005, Aldo et al, 2010, Nakada et al, 2009. Our findings show substantial discrepancy between primary first trimester trophoblasts and the trophoblast cell line BeWo, with regards to both TLR gene expression and function, and this unresponsiveness of BeWo cells to TLR activation is supported by others (Fujisawa et al, 2000, Komine-Aizawa et al, 2008.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Data from trophoblast cell lines, including BeWo cells, dominate previous reports on TLR function in early gestational trophoblasts (Komine-Aizawa et al, 2008, Klaffenbach et al, 2005, Aldo et al, 2010, Nakada et al, 2009. Our findings show substantial discrepancy between primary first trimester trophoblasts and the trophoblast cell line BeWo, with regards to both TLR gene expression and function, and this unresponsiveness of BeWo cells to TLR activation is supported by others (Fujisawa et al, 2000, Komine-Aizawa et al, 2008.…”
Section: Discussionsupporting
confidence: 75%
“…and TLR10 expression have been demonstrated in primary first trimester trophoblasts (Abrahams et al, 2004, Mulla et al, 2013 and of the endosomal TLRs, only TLR3 and TLR8 transcripts have been detected in early gestational placentas (Abrahams et al, 2005, Aldo et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Ten different human TLRs, each responding to a specific set of ligands, have been identified [4]. TLR expression and activation in primary trophoblasts [5][6][7][8][9][10] may contribute substantially to development of inflammatory pregnancy complications such as preeclampsia [11][12][13]. In Tangerås/Stødle et al [7] we demonstrated a broad functional TLR profile in primary first trimester trophoblasts, while the trophoblast cell line BeWo showed no TLR mediated cytokine response.…”
Section: Introductionmentioning
confidence: 95%
“…Nonetheless, given the extensive communication between mother and embryo, we did expect to see some maternal response to the infected embryo. We tried to search for this response in the placenta, since the organ contains the maternal tissue that is in closest proximity to the infected embryo and is certainly capable of mounting an innate response (62,63). Surprisingly, the data indicated a minimal placental response.…”
Section: Discussionmentioning
confidence: 99%